Educational Reform in Chile - Marta Quiroga Lobos (Pedagogika)
This study aims to analyse, within the context of paradox theory, the tensions and opportunities introduced by the meetings of microcentres, as spaces for teacher professional development within an educational reform. After a qualitative study, it was concluded that four types of paradox are present: organisation, learning, belonging, and performance. Additionally, the microcentres are sites of negotiation between local autonomy and state control.